Estimation of above-ground carbon of mangrove forest using Sentinel-1 (SAR) and field inventory data: a case study in Quang Yen, Quang Ninh province - Hai Hoa, Nguyen; The Doi, Bui; Van Truong, Vu; Duc Le, Phan; Tri Son, Ha (Journal of Forestry Science and Technology, 2023)
Tide-dominated mangroves are found along shallow shorelines with modest slope where they receive freshwater runoff and nutrients from rainfall. They have been globally recognized as they play a vital role in preventing coastal erosion, mitigating effects of wave actions, and protecting coastal habitats and adjacent shoreline land-uses from extreme coastal events. By using Sentinel-1A data, the study has constructed the spatial distribution of mangrove cover compared to PlanetScope image in Quang Yen. In fact, this study used the Sentinel-1A-derived VV/VH polarizations for mangrove cover mapping with thresholds of -12.8<VH<-3.8 and -16.65<VV<-3.3. Upon using VV and VH polarizations for mangrove cover mapping compared to PlanetScope data, it has been confirmed that these polarizations are suitable for mangrove cover monitoring along the coast of Quang Yen with overall accuracy over 92.0% and Kappa coefficient greater than 0.80 in 2022. This study also developed mangrove AGB models based on the field survey data and SAR data for estimating AGB and AGC of mangrove forests in Quang Yen. Overall, selected AGB models (AGB = 288.17 + 21.57*VV, R2=0.553, p-value<0.001) have provided promising options for carbon estimation and monitoring to the coastal areas where the cloudy cover is mostly present and optical remote sensing data is usable. To have more accurate AGB models based on SAR data, this study also suggests that further study should be carried out using more advanced machine learning models based on Sentinel-1A and Sentinel-1B for carbon estimation of mangrove forests in Quang Yen.